TERIKATNYA NEGARA DALAM PERJANJIAN INTERNASIONAL - Danel Aditia Situngkir (Universitas Kristen Satya Wacana, 2018)
This paper discusses the issue of the binding of the state in international agreements. The more complex the relations between international legal subjects making international customs can no longer be used to resolve the various problems that arise. In modern international relations, the existence of international treaties is mandatory. The issues discussed in this paper are the role of the state in international treaties and how the state is bound in international treaties. Both of these issues are examined with normative juridical approaches based on legal theory, legal principles, international law sources and international agreements. From the discussion it was concluded that the role of the state in international agreements will influence the actions of the state against international agreements. The binding of the state in international agreements is caused by the actions of the state and the contents of international agreements. a third country may be bound by the contents of an international treaty if the norm set forth therein is part of the jus cogens.